Gastroesophageal Reflux Disease Questionnaire (GerdQ) is an Easy and Useful Tool for Assessing GERD - Ari Fahrial Syam (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2015)
-